Effect of Soil Depth on Early Performance and Characteristics of Roots of some Tree Species on a Hill Slope - Singh, K. A. (Indian Journal of Agroforestry, 2020)
A field experiment was conducted on the effects of soil depths on root characteristics and biomass productivity of four tree species (Pinus kesiya, Royte ex. Parie, Michelia champaca L., Grevilea robusta A. cunn and Cupressus torulosa D. Don) planted on a hill slope. Changes in root characteristics revealed that vertical penetration of main root, number of roots and root weight per plant increased in proportion to soil depth occupied by the tree species. The main root changed its course of orientation sensing impediments and moved down the hill slope. Mean root spread decreased significantly in the deep soil in case of M. Champaca and P. kesiya but it increased marginally in case of G. robusta and C. torulosa as compared to shallow soils. Broad leaved M. champaca and G. robusta had reduced root length, thicker proximal diameter of main and lateral roots in shallow soils while in pine group of plants, either length of main root was shorter in deep soil than the shallow soil as in case of P. kesiya or there was not any significant difference in root length as in case of C. torulosa, both the tree species also grew thicker roots in the deep soils. Effect of soil depth on plant growth became evident 18 months after planting. The differential behaviour of tree species in response to soil depths indicated their adaptation and success on the hill slopes through changes in root characteristics particularly root spread and modification in different parts of shoot i.e. basal and breast height diameters, number of branches per plant, canopy length in case of broad leaved tree species and canopy length and canopy diameter both in case of pine group of tree species. Thus, the little difference in root number under different soil depths and tendency to spread extensively under shallow soil depth leading to minimal variation in total biomass productivity helped P. kesiya to be most adaptive on the shallow soils of the hill slopes followed by M. champaca, a broad leaved tree species.